(untitled) (Research, Society and Development, 2022)
This research is bound to the Graduated Program in Science and Mathematics at the Franciscan in the Professional University in the Professional Master’s Course in Science and Mathematics Teaching. The research aims to: Understand how playfulness can enhance interdisciplinary teaching in the area of Natural Sciences in the fourth year of elementary school; Reflecting about the importance of interdisciplinarity in learning, understand the development of learning from the perspective of playfulness; Contextualizing the interdisciplinary knowledge of specific Nature Content in the fourth year of Elementary School. This study has a qualitative approach and the methodology applied is the Design-Based Methodology which is presented in four phases: analysis of the educational proposition;; deployment of the pedagogical artifact; intervention and deployment of the progress of on design principle. By means of participant observation, an educational product was developed in agreement with the National Common Curricular Base - BNCC - with the goal of analysing the impact on Learning in Science Teaching. Having the understanding that the Interdisciplinare, the Playfulness and the Science Teaching are of substantial importance to emphasize Learning, because by using Playfulness and their pedagogical practices, the teacher is able to work better in a pleasant way and make the classes more attractive and efficient. This is what was found during the research in the fourth year of Elementary School.